The Pedagogy of Play: The Joy of Living, Learning, and Riding Motorcycles - Jeffrey Zacharakis (Adult Education Research Conference, 2018)
This research explores how the theoretical construct of lifelong learning is enriched through play, and proposes that the pedagogy of play might be an important new adult learning theory.
Keywords: adult learning; pedagogy of play; motorcycling; Legos